Temporal adaptation to audiovisual asynchrony generalizes across different sound frequencies - Navarra, Jordi; García-Morera, Joel; Spence, Charles (Frontiers in Psychology, 2012)
The human brain exhibits a highly-adaptive ability to reduce natural asynchronies between visual and auditory signals. Even though this mechanism robustly modulates the subsequent perception of sounds and visual stimuli, it is still unclear how such a temporal realignment is attained. In the present study, we investigated whether or not temporal adaptation generalizes across different sound frequencies. In a first exposure phase, participants adapted to a fixed 220-ms audiovisual asynchrony or else to synchrony for 3min. In a second phase, the participants performed simultaneity judgments (SJs) regarding pairs of audiovisual stimuli that were presented at different stimulus onset asynchronies (SOAs) and included either the same tone as in the exposure phase (a 250Hz beep), another low-pitched beep (300Hz), or a high-pitched beep (2500Hz). Temporal realignment was always observed (when comparing SJ performance after exposure to asynchrony vs. synchrony), regardless of the frequency of the sound tested. This suggests that temporal recalibration influences the audiovisual perception of sounds in a frequency non-specific manner and may imply the participation of non-primary perceptual areas of the brain that are not constrained by certain physical features such as sound frequency.